Evaluation for sustainability of machining processes in Indian small scale industries. (2020) - Agrawal, Rishabh; Kiran Chaganti, Phaneendra; Mohan Reddy Nune, Madan
Abstract: Machining industries form a major part of small and mediocre scale industries in India. Also, the wastes generated and the resources consumed by these industries are quite significant. Due to the expansion of industries in recent years, there has been an adverse impact on the environment. Renewable resources are getting exhausted at a rate which is greater than the rate of their regeneration, and wastes are being produced at a rate which is far higher than the rate at which current waste management techniques work. In this context, sustainability for a machining industry has become a necessity, rather than just a choice. This work aims at studying some of the existing practices in small-scale Indian machining industries, and comparing the various available alternatives. Critical parameters for sustainability like spindle power, average time period of operation of the machine (hours), amount of waste produced (kg), cost of raw material, cost of tooling, cost of maintenance and cost of waste management were simultaneously considered. The available alternatives were compared using various Multi-Attribute Decision Making (MADM) methods like TOPSIS and AHP. In addition to this, this paper intends to introduce some sustainability solutions with the perspective of cost minimization. The solutions in this work are suggested while considering society, environment and economy simultaneously. This paper suggests the appropriate ways to communicate the obtained results to the decision makers of small-scale industries. This paper gives a scope to small scale industries in improving the sustainability